Five-Year Outcome after Coronary Artery Bypass Surgery in Survivors of Out-of-Hospital Cardiac Arrest - Mosorin, Matti-Aleksi; Lantos, Maté; Juvonen, Tatu; Biancari, Fausto (Frontiers in Surgery, 2015)
Objective: The aim of this study is to evaluate the role of coronary artery bypass grafting (CABG) in patients with out-of-hospital cardiac arrest (OHCA). Methods: The immediate and 5-year outcome after CABG of a consecutive series of 48 patients who survived OHCA were compared with those of control patients having had a recent myocardial infarction without ventricular arrhythmias. Results: All OHCA patients were found to have suffered myocardial infarction-related cardiac arrest. The mean delay from OHCA to CABG was 10.3±13.0 days. Despite not statistically significant, the risk of 30-day postoperative mortality was higher among OHCA patients than control patients (6.3% vs. 0%, p=0.24, propensity score adjusted analysis: p=1.00). Cardioverter defibrillator was implanted in two patients who were alive 3.8 and 4.4 years after CABG, respectively. At 5-year the overall survival rate was 80.7% in OHCA patients and 84.5% in control patients (p=0.98, propensity score adjusted analysis: p=0.87), and survival freedom from fatal cardiac event was 86.1% in OHCA patients and 86.5% in control patients (p=0.61; propensity score adjusted analysis: p=0.90). Conclusions: Early and 5-year survival rates after CABG in OHCA patients are excellent even when cardioverter defibrillator is very selectively implanted. Such good early and intermediate results observed after CABG suggest a confident approach toward surgical revascularization also in this critically ill patient population.